Structure and pharmacological activities of polysaccharides from Anoectochilus roxburghii (Wall.) Lindl. (December 2021) - Wu, Tong; Li, Shuailing; Huang, Yuqiu; He, Zhen; Zheng, Ying; Stalin, Antony; Shao, Qingsong; Lin, Ding
Graphical abstract: Highlights: Structure of A. roxburghii polysaccharides was characterized by various techniques. A. roxburghii polysaccharides relieved the fatigue of mice from swimming. A. roxburghii polysaccharides showed potential antioxidant activity on model mice. A. roxburghii polysaccharides prolonged the survival time of hypoxic mice. Abstract: Anoectochilus roxburghii (Wall.) Lindl is a perennial herb of Orchidaceae, which was regarded as a widely favorite functional food. A. roxburghii polysaccharides, possessing multitudinous activities, are one of the most important bioactive components of A. roxburghii . To promote the research and application of A. roxburghii polysaccharides, the structure of polysaccharides was analyzed by Fourier-transform infrared spectra, atomic force microscopy, and gas chromatography. Besides, the anti-fatigue, anti-oxidation, and anti-hypoxia effects of polysaccharides were evaluated. The results showed that the structure of A. roxburghii polysaccharides was rod-like aggregate, with no branching, and the size was uniform. A. roxburghii polysaccharides were mainly composed of rhamnose, arabinose, xylose mannose, glucose and galactose in the molar ratio of 0.28: 1.93: 2.06: 2.40: 1.00: 6.43. In vivo experiments in mice proved that it exhibited good anti-fatigue, anti-oxidation and anti-hypoxia activities. Overall, the results suggested that A. roxburghii polysaccharides may serve as potential functional food and medicine.